Analisis Perencanaan Kota Layak Anak di Kota Semarang - Vika Restu Dian Saputri; Dewi Rostyaningsih; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2014)
In the development of Child-Friendly City in region such as mandated by the Minister of women's empowerment and the protection of the Republic of Indonesia Regulation that planning is one of the stages that must be done by the region through the drafting of action plans The Child-Friendly City. In Semarang City, experienced delays in making Local Action Plan of Child-Friendly City. The main purpose of this research to formulate a strategy of policy and program planning of Child-Friendly City in Semarang City that described in the discussion.  This research based on  theory of M. Manullang, William N. Dunn, T.Hani, dan  Mamduh. The research method used is descriptive-qualitative. While data mining is carried out through in-depth interviews to informants and some of the data and documents to support the completeness and depth of the information required.   Based on research results, the commitment of stakeholders are still low. There was Child-friendly city policy in Semarang city is also not yet known and understood by all stakeholders especially in village and services centre stages. It is visible from a lack of coordination of the stakeholders and the programs was not done according to the plan, example the hours learning child program. According to the Mayor's Regulations Number 20 in 2010 about Child-Friendly City Policies through Child-friendly Village approach, but the implementation of Child-Friendly subdistrict/village still being stagnant. The research is also produce forecasting of the future policy with two alternatives, namely the preparation of the budget and the allocation of RAD.  Based on result of research can be produced the policy strategy and program planning that planned covering institutional and fifth cluster with reference to programs planned by a city government in RAD KLA Semarang City thus produced program planning that is different from that are found on RAD KLA.